Evaluating the Effects of Sediment Transport on Pipe Flow Resistance - Vito Ferro (Water, 2021)
In this paper, the applicability of a theoretical flow resistance law to sediment-laden flow in pipes is tested. At first, the incomplete self-similarity (ISS) theory is applied to deduce the velocity profile and the corresponding flow resistance law. Then the available database of measurements carried out by clear water and sediment-laden flows with sediments having a quasi-uniform sediment size and three different values of the mean particle diameter Dm (0.88 mm, 0.41 mm and 0.30 mm) are used to calibrate the Γ parameter of the power-velocity profile. The fitting of the measured local velocity to the power distribution demonstrates that (i) for clear flow the exponent δ can be estimated by the equation of Castaing et al. and (ii) for the sediment-laden flows δ is related to the diameter Dm. A relationship for estimating the parameter Гv obtained by the power-velocity profile and that Гf of the flow resistance law is theoretically deduced. The relationship between the parameter Гv, the head loss per unit length and the pipe flow Froude number is also obtained by the available sediment-laden pipe flow data. Finally, the procedure to estimate the Darcy-Weisbach friction factor is tested by the available measurements.